CRISPR/Cas9-mediated targeted mutagenesis of FAD2-1 gene for oleic acids composition in sunflower - AYDİN, YILDIZ; ALTINKUT UNCUOĞLU, AHU (My University, 2022)
Sunflower (Helianthus annuus L.) is the most widespread plant used for production of oil among all oilseeds cultivated in Turkey in terms of agricultural area and production. Sunflower with high oleic acid content is always desirable because of benefits on health and industrial use. The enzyme FAD2-1 catalyzes the conversion of oleic acid to linoleic acid in sunflower. The fatty acid composition can be enhanced by gene editing of FAD2-1 gene by CRISPR/Cas9 technique which has been applied recently as a new breeding technique to improve productivity and enhance sustainability in agriculture. Hence, CRISPR/Cas9 genome editing systems were utilized to knockout the FAD2-1 gene in order to increase production of oleic acid content. For this purpose, two low oleic sunflower genotypes were transformed with two sgRNA that target FAD2-1 gene. sgRNA expression cassettes were assembled into the binary vector by Golden Gate assembly in a single reaction which is followed by A. tumefaciens-mediated transformation and in vitro germination. Putatively transformed shoots were selected with A. tumefaciens-mediated the optimized kanamycin concentration (100 mg/L) in the medium. The challenges of transformation of sunflower were summarized and possible solutions were proposed. This study indicated that sunflower still can be modified by CRISPR/Cas9 genome editing system to develop high oleic sunflower.
Keywords: Sunflower; CRISPR/Cas9; Genome editing; Oleic acid; FAD2-1 gene; Agrobacteriummediated transformation